Los juegos de la memoria: los usos públicos de San Martin en las liturgias estatales argentinas (siglos xx y xxi) - Beatriz Bragoni (Caravelle)
This paper deals with semantic variations and monumental representations of San Martín among Argentinian state’s liturgies between the 19th century and today in order to analyze the relationship between changing institutional contexts and political as well as intellectual operations revolving around a fixed radication in national imagination and public uses of his image established by state elites and social groups which strengthened the political and cultural fight in contemporary Argentina.